PENGARUH SALES PROMOTION DAN STORE ATMOSPHERE TERHADAP SHOPPING EMOTION DAN IMPULSE BUYING PADA GIANT PEKANBARU - Kurniawati, Devi; Restuti, Sri (Jurnal Tepak Manajemen Bisnis, 2014)
the purpose of this study was to determine the effect of sales promotion and store atmosphere on shopping emotion and impulse buying at Giant Pekanbaru. Collecting data using a questionnaire with sample of 150 respondents who are customers of Giant Pekanbaru with convenience sample method. The technique of data analysis using Structural Equation Modeling (SEM) of a statistical software package AMOS. The results of the analysis prove that the sales promotion and store atmosphere positive and significant effect on emotion shopping. Sales promotion and store atmosphere are carried by Giant to increase a feeling of satisfaction, feeling comfortable and enjoi when shopping at Giant. Meanwhile, sales promotion and store atmosphere positive effect but not significant to impulse buying. Sales promotion and store atmosphere that was done by a Giant not make customers buy goods outside of the planned shopping list (impulse buying). Shopping emotion positive and significant effect on impulse buying. Giant priorities to increase impulse buying is to create shopping emotion first. Shopping emotion can be established by observing the atmosphere inside and outside outlets like music, design outlets and entrances. Giant also have to make more variations of sales promotions that will attract customers to continue to shop like a free sample multiply and hold a member card.Keywords : Sales Promotion , Store Atmosphere, Shopping Emotion and Impulse Buying